2000
DOI: 10.2337/diabetes.49.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of IGF-I on type 2 nitric oxide synthase expression in Ins-1 cells and protection against activation-dependent apoptosis: involvement of phosphatidylinositol 3-kinase.

Abstract: 2 2 heterotetrameric molecule, through its ligand-induced tyrosine kinase activity, leading to the phosphorylation of the cytoplasmic domain of the -subunits (6,7). Receptor activation promotes the rapid phosphorylation on multiple tyrosine residues of insulin receptor substrate (IRS)-1 and I R S-2, which allows the binding, through the phosphorylated sequences, of s r c homology domain 2 (SH2) domains of various proteins, initiating further IGF-I-dependent signaling events (8,9). Among the proteins interactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
(36 reference statements)
3
33
0
Order By: Relevance
“…As shown in Fig. 2, a prominent increase in caspase 3 activity (three-fourfold) was observed after treating the beta-cells with the cytokine combination IL-1β/IFN-γ or palmitic acid, respectively, in agreement with data reported in the literature [11,23]. Exposure of INS-1 cells to leptin or gAcrp30 did not modify caspase 3 activity under control conditions (not shown in the Figure).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Fig. 2, a prominent increase in caspase 3 activity (three-fourfold) was observed after treating the beta-cells with the cytokine combination IL-1β/IFN-γ or palmitic acid, respectively, in agreement with data reported in the literature [11,23]. Exposure of INS-1 cells to leptin or gAcrp30 did not modify caspase 3 activity under control conditions (not shown in the Figure).…”
Section: Resultssupporting
confidence: 89%
“…The proapoptotic role of the NF-κB pathway in response to proinflammatory cytokines is well established in pancreatic beta cells [7,8,9,10,11]. Recent work also indicates a direct involvement of this transcription factor in the regulation of beta-cell lipotoxicity [6].…”
Section: Effect Of Leptin and Gacrp30 On Cytokine-and Fatty Acid-indumentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, exendin-4 treatment was also able to reduce the effects of cytokines on apoptosis in cells infected with constitutively-active PKB, although the protective effects of exendin-4 were not observed in all Adv-CA cells, possibly due to the extremely high levels of activated PKB already present. Nonetheless, in agreement with the finding of an important role for PKB in GLP-1 signalling, it has been shown that inhibition of PI3-K, the upstream regulator of PKB activity [23], decreases the IGF-1-mediated protection of beta cells against cytokines [41,42]. IGF-1 is a known regulator of PI3-K/PKB, whereas the mechanisms that link the G protein-coupled GLP-1 receptor to cell survival pathways are not well understood.…”
Section: Discussionsupporting
confidence: 78%
“…Nonetheless, the changes in iNOS in response to cytokines were paralleled by decreased intracellular levels of ROS. Furthermore, similar studies have shown that the iNOS/nitric oxide-induced apoptosis of INS-1 cells can be prevented by IGF-1, through a PI3-Kdependent pathway [42]. These findings suggest that iNOS may be a target gene for the PKB signalling pathway.…”
Section: Discussionmentioning
confidence: 58%